Proteome Modulation in Peripheral Blood Mononuclear Cells of Peste des Petits Ruminants Vaccinated Goats and Sheep - Wani, Sajad Ahmad; Sahu, Amit Ranjan; Khan, Raja Ishaq Nabi; Praharaj, Manas Ranjan; Saxena, Shikha; Rajak, Kaushal Kishor; Muthuchelvan, Dhanavelu; Sahoo, Aditya; Mishra, Bina; Singh, R. K.; Mishra, Bishnu Prasad; Gandham, Ravi Kumar (Frontiers in Veterinary Science, 2021)
In the present study, healthy goats and sheep (n=5), confirmed negative for PPRV antibodies by monoclonal antibody based competitive-ELISA and by serum neutralisation test, and for PPRV antigen by s-ELISA were vaccinated by Sungri/96. A quantitative study was carried out to compare the proteome of PBMCs of vaccinated goat and sheep (5dpv and 14pv) versus unvaccinated (0 day ) to divulge the alteration in protein expression following vaccination. A total of 232 and 915 proteins were differentially expressed at 5dpv and 14dpv, respectively in goats. Similarly, 167 and 207 proteins were differentially expressed at 5dpv and 14dpv, respectively in sheep. Network generated by Ingenuity pathway analysis was “infectious diseases, antimicrobial response and inflammatory response” which include the highest number of focus molecules. The bio functions, cell-mediated immune response and humoral immune response were highly enriched in goats at 5 dpv and t 14 dpv. At molecular level, immune response produced PPRV vaccine virus in goats is effectively coordinated and stronger than in sheep, though the vaccine provides protection from virulent virus challenges in both. The altered expression of certain PBMCs proteins especially ISG15 and IRF7 induce change in marked changes in cellular signalling pathways to coordinate host immune responses.